Enhancing dragon fruit (Hylocereus costaricensis) with vermicompost and biofertilizer: A study on physico-chemical improvements - PRATAP, RAVI; TRIPATHI, V K (The Indian Journal of Agricultural Sciences, 2025)
An experiment was conducted during 2022 and 2023 at Chandra Shekhar Azad University of Agriculture and Technology, Kanpur, Uttar Pradesh to evaluate the impact of vermicompost and biofertilizers on the physical and chemical characteristics of dragon fruit, providing valuable insights into sustainable cultivation practices using 11 treatments, viz. T1, Control; T2, Vermicompost (0.5 kg/plant); T3, Azotobacter (50 g/plant); T4, Azospirillum (50 g/plant); T5, Phosphate solubilizing bacteria (50 g ); T6, Vermicompost (0.5 kg/plant) + Azotobacter (50 g/plant); T7, Vermicompost (0.5 kg/plant) + Azospirillum (50 g/plant); T8, Vermicompost (0.5 kg/plant) + Phosphate solubilizing bacteria (50 g/plant); T9, Vermicompost (0.5 kg/plant) + Azotobacter (50 g/plant) + Azospirillum (50 g/plant); T10, Vermicompost (0.5 kg/plant) + Azotobacter (50 g/plant) + Phosphate solubilizing bacteria (50 g/plant) and T11, Vermicompost (0.5 kg/plant) + Azospirillum (50 g/plant) + Phosphate solubilizing bacteria (50 g/plant). The experiment was laid out in randomized block design (RBD) with three replications. The significant differences in physico-chemical attributes of dragon fruit (Hylocereus costaricensis L.), were observed as influenced by vermicompost and biofertilizers application. The maximum length of fruit (8.96 cm), diameter (7.55 cm), weight (205.90 g), volume (162.33 cc), specific gravity (1.27), pulp weight (160.55 g) and peel weight (41.59 g), pulp: peel ratio (3.86), thickness of fruit pulp (6.84 cm), thickness of fruit peel (0.59 cm) and number of bracts/fruit (30.99) and in biochemical parameters, total soluble solids contents (14.80 °Brix), titratable acidity (0.39%), ascorbic acid content (9.42 mg/100 g), total sugars (9.40%), reducing sugar (5.23%) and non-reducing sugar (4.17%) were found elevated with the use of vermicompost (0.5 kg/plant) + Azospirillum (50 g/plant) + Phosphate solubilizing bacteria (50 g/plant).